2021
DOI: 10.7554/elife.69796
|View full text |Cite
|
Sign up to set email alerts
|

Developmental change in prefrontal cortex recruitment supports the emergence of value-guided memory

Abstract: Prioritizing memory for valuable information can promote adaptive behavior across the lifespan, but it is unclear how the neurocognitive mechanisms that enable the selective acquisition of useful knowledge develop. Here, using a novel task coupled with functional magnetic resonance imaging, we examined how children, adolescents, and adults (N = 90) learn from experience what information is likely to be rewarding, and modulate encoding and retrieval processes accordingly. We found that the ability to use learne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 119 publications
2
5
0
Order By: Relevance
“…Consistent with previous research in adults, we found increased brain activation in several cortical areas and the thalamus across participants of all ages for encoding high-relative to lowreward associations (Wittmann et al, 2005;Cohen et al, 2014;. We focused specifically on observed dlPFC activation given both prior work in adults underscoring its role in driving reward-motivated behaviors (Ballard et al, 2011), as well as evidence of its protracted developmental trajectory (Mills et al, 2014) and increasing contributions to memory encoding with age (Menon et al, 2005;Ofen et al, 2007;Ghetti et al, 2010;Nussenbaum and Hartley, 2021). We found that dlPFC activation was related to high-reward specific associative memory benefits 24 hours after encoding across all participants.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with previous research in adults, we found increased brain activation in several cortical areas and the thalamus across participants of all ages for encoding high-relative to lowreward associations (Wittmann et al, 2005;Cohen et al, 2014;. We focused specifically on observed dlPFC activation given both prior work in adults underscoring its role in driving reward-motivated behaviors (Ballard et al, 2011), as well as evidence of its protracted developmental trajectory (Mills et al, 2014) and increasing contributions to memory encoding with age (Menon et al, 2005;Ofen et al, 2007;Ghetti et al, 2010;Nussenbaum and Hartley, 2021). We found that dlPFC activation was related to high-reward specific associative memory benefits 24 hours after encoding across all participants.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with previous research in adults, we found increased brain activation in several cortical areas and the thalamus across participants of all ages for encoding high-relative to lowreward associations (Wittmann et al, 2005;Cohen et al, 2014;. We focused specifically on observed dlPFC activation given both prior work in adults underscoring its role in driving reward-motivated behaviors (Ballard et al, 2011), as well as evidence of its protracted developmental trajectory (Mills et al, 2014) and increasing contributions to memory encoding with age (Menon et al, 2005;Ofen et al, 2007;Ghetti et al, 2010;Nussenbaum and Hartley, 2021). We found that dlPFC activation was related to high-reward specific source memory benefits 24 hours after encoding across all participants.…”
Section: Discussionsupporting
confidence: 82%
“…We speculate children's lack of differentiation reflects limitations in these prefrontal and hippocampal mechanisms. Prior work indicates strategic memory processes increase into adulthood (Bjorklund et al., 2009) and are associated with changes in prefrontal structure (Yu et al., 2018) and function (Nussenbaum & Hartley, 2021). There are also age‐related increases in the degree to which prefrontal function during encoding—perhaps reflecting engagement in strategies—predicts subsequent memory between late childhood and adulthood (Ofen et al., 2007; Shing et al., 2016; see Ghetti & Fandakova, 2020 for review).…”
Section: Discussionmentioning
confidence: 99%